Symmetric Point Structure of Superconvergence for Cubic Triangular Elements—A Consultation with Zhu (Journal of Computational Mathematics, 2021)
Superconvergence structures for rectangular and triangular finite elements are summarized. Two debatable issues in Zhu's paper [18] are discussed. A superclose polynomial to cubic triangular finite element is constructed by area coordinate.